2001
DOI: 10.2472/jsms.50.1091
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue. Effects of Prestraining on High Cycle Fatigue Strength of High Strength Low Alloy TRIP Steels.

Abstract: The effects of prestraining on high cycle fatigue strength of newly developed low alloy TRIP steels with different matrix structure and different retained austenite characteristics were investigated for the automotive applications. The prestraining to 10% in tension increased fatigue limit of the TRIP steels, especially in steel with polygonal ferrite matrix. It was considered that the polygonal ferrite matrix in the steel brought high fatigue limit mainly due to TRIP of the retained austenite and high compres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…It is very difficult to compare the fatigue limits of TM steels with other AHSSs because fatigue tests are not conducted under the same fatigue mode and stress ratio. However, from comparison of several references [1,4,6,7,9,27,28,41,42,[44][45][46][47][48], we can conclude that TM steels possess the high fatigue limits compared to the conventional quenched and tempered martensitic steels, in the same In general, fatigue limits of smooth and notched specimens are principally controlled by fatigue crack initiation and propagation stages, respectively. Figure 10a shows a SEM image illustrating a fatigue crack initiated on the surface of a notched specimen of TM steel [13].…”
Section: Fatigue Propertiesmentioning
confidence: 83%
See 3 more Smart Citations
“…It is very difficult to compare the fatigue limits of TM steels with other AHSSs because fatigue tests are not conducted under the same fatigue mode and stress ratio. However, from comparison of several references [1,4,6,7,9,27,28,41,42,[44][45][46][47][48], we can conclude that TM steels possess the high fatigue limits compared to the conventional quenched and tempered martensitic steels, in the same In general, fatigue limits of smooth and notched specimens are principally controlled by fatigue crack initiation and propagation stages, respectively. Figure 10a shows a SEM image illustrating a fatigue crack initiated on the surface of a notched specimen of TM steel [13].…”
Section: Fatigue Propertiesmentioning
confidence: 83%
“…It is very difficult to compare the fatigue limits of TM steels with other AHSSs because fatigue tests are not conducted under the same fatigue mode and stress ratio. However, from comparison of several references [1,4,6,7,9,27,28,41,42,[44][45][46][47][48], we can conclude that TM steels possess the high fatigue limits compared to the conventional quenched and tempered martensitic steels, in the same way as several AHSSs such as TBF steels [1,4,6,7,9], Q&P steels [27,28] and nanostructured bainitic steels [41,42,[44][45][46][47][48][49].…”
Section: Fatigue Propertiesmentioning
confidence: 89%
See 2 more Smart Citations
“…It has been reported that the behavior of fatigue crack propagation in TRIP-aided steels depends on (ⅰ) the plastic deformation resistance of the matrix and transformed martensite and (ⅱ) the relaxation of stress concentration due to the strain-induced transformation of the retained austen- ite. [21][22][23] Regarding (ⅰ) the plastic deformation resistance of the matrix, a high crack propagation resistance might be obtained in the TM and the TBM steels. This occurs because the TM steels with martensite matrix and the TBM steels with martensite-bainitic ferrite matrices exhibited higher TS than the TBF steels with bainitic ferrite matrix.…”
Section: Effect Of Matrix Morphologymentioning
confidence: 99%